Demographic study and management of colonic atresia: Single-center experience with review of literature - Hinglaj Saha; Dipak Ghosh; Tapanjyoti Ghosh; Shibshankar Burman; Kaushik Saha (Wolters Kluwer Medknow Publications, 2018)
Context and Aim: The aim of this study is to highlight the rarity of this disorder and its associated anomalies and our objective was to review our experience in the management of colonic atresia (CA) with respect to staged surgery versus one-step procedure for a better outcome of the disease. Settings and Design: A randomized, controlled, single-center study conducted over a period of 4 years from October 2013 to 2017. Subjects and Methods: Nine cases were operated for CA of which three underwent primary anastomosis and six underwent initial colostomy followed by definitive surgery. Age, sex, body weight, clinical presentation, type of atresia, site, time interval of operation, associated anomalies, initial procedure, postoperative complications, final procedure, biopsy, hospital stay, and outcome were noted. Statistical Analysis Used: Microsoft Excel was used for statistical analysis. Results: Out of 9 patients, 6 were males and 3 were females, 7 patients survived and 2 patients died (mortality 22.2%), of which one patient with primary anastomosis had leak and sepsis and one patient with primary anastomosis had associated Hirschsprung's disease (HD). Mean time gap for operation was 12.8 h and mean hospital stay was 3.5 days for initial colostomy and 21 days for primary anastomosis. Wound dehiscence occurred in 4 patients. Malrotation was found in 3 patients, HD in 2 patients, cardiac anomaly in 2, Meckel's diverticulum in 1, and cleft lip in 1 patient. Type IIIa atresia was found in in 6 patients, Type I in 2, and Type II in 1 patient. The most common site was transverse colon (n = 5). Conclusion: Diagnosis and management of CA is a challenge. Early presentation and diagnosis should be prompt. Staged procedure with initial colostomy followed by definitive procedure is the preferred choice. Associated anomaly HD must be ruled out.